Scientific research work of students in the specialist education training system: regulation and legal regulation - Verba, Snizhanna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article presents the results of a study of the problem of regulatory and legal support of students᾽ research work in the process of studying at a higher education institution. Positives and gaps in the current legislation are highlighted. It is noted that there is a legal conflict in the normative acts of Ukraine. The legislation of Ukraine does not classify students as subjects of scientific activity. At the same time, at the level of by-laws and internal acts of the Higher Education Institution, student research is separately provided for as a separate type of their scientific activity, and students themselves are defined as the subjects of such activity.As a result of the study, a number of practical recommendations were formulated. The Law of Ukraine «On Scientific and Scientific-Technical Activities» should provide for the subjectivity of students as participants in scientific research activities, primarily at the level of higher education institutions. In the Law of Ukraine «On Higher Education»: clearly provide for the implementation of the principle of integration of educational, scientific and educational work at all stages and levels of the educational process; to expand the status of students to subjects of scientific activity within the framework of the National Academy of Higher Education with the corresponding rights and obligations; to provide a detailed list of forms and mechanisms of student involvement in the NDR of higher education both during the educational process (as a mandatory type of activity) within the framework of the implementation of the curriculum, and in extracurricular time (on a voluntary basis). In the «Regulations on the Organization of Scientific, Scientific and Technical Activities in Higher Educational Institutions of III and IV Levels of Accreditation», the Ministry of Education and Culture of Ukraine defines the department as the main structural-organizational and executive unit for the conduct of student development in the structure of higher education institutions with the corresponding rights and responsibilities. It is proposed to expand the existing normative and organizational system of encouraging students and their academic supervisors from among the teaching staff (including material ones) for the implementation of scientific research works at the expense of state and non-state funds, the possibilities of grant programs, to provide for an increase in the weight of the indicators of the student᾽s NDR when conducting scientific attestation of ZVO.